Metabolic Dysfunction in Hutchinson–Gilford Progeria Syndrome - Ray Kreienkamp; Susana Gonzalo (Cells, 2020)
Hutchinson−Gilford Progeria Syndrome (HGPS) is a segmental premature aging disease causing patient death by early teenage years from cardiovascular dysfunction. Although HGPS does not totally recapitulate normal aging, it does harbor many similarities to the normal aging process, with patients also developing cardiovascular disease, alopecia, bone and joint abnormalities, and adipose changes. It is unsurprising, then, that as physicians and scientists have searched for treatments for HGPS, they have targeted many pathways known to be involved in normal aging, including inflammation, DNA damage, epigenetic changes, and stem cell exhaustion. Although less studied at a mechanistic level, severe metabolic problems are observed in HGPS patients. Interestingly, new research in animal models of HGPS has demonstrated impressive lifespan improvements secondary to metabolic interventions. As such, further understanding metabolism, its contribution to HGPS, and its therapeutic potential has far-reaching ramifications for this disease still lacking a robust treatment strategy.